Islamic Education Management Based on Nahdiyah ValuesThe Perspective of Nahdlatul Ulama Scholars - Saefrudin Saefrudin (Maneggio, 2026)
This study aims to comprehensively examine the management of Islamic education based on Nahdiyah values ​​from the perspective of Nahdlatul Ulama (NU) scholars. Nahdlatul Ulama, as the largest Islamic organization in Indonesia, is rooted in Nahdiyah values, including tawassuth (moderation), tawazun (balance), i'tidal (justice), tasamuh (tolerance), amanah (trustworthiness), and shura (shura), which serve as the philosophical foundation for the management of Islamic educational institutions. Through a systematic literature review approach of 40 relevant scientific sources published between 2021 and 2026, this study analyzes how Nahdiyah values ​​are implemented in the management of curriculum, leadership, human resources, finance, and organizational culture in NU educational institutions. The results of the study indicate that management of Islamic education based on Nahdiyah values ​​produces educational institutions that excel academically and are strong in character, with a leadership system based on authoritative yet participatory kiai (Islamic scholars), a curriculum that integrates religious and general knowledge in a balanced manner, and a pesantren culture that is resilient to changing times. The practical implications of this study point to the importance of formalizing the Nahdiyah value-based management model as a paradigmatic alternative for managing Islamic education in Indonesia that is able to answer the challenges of modernity without losing its identity.